PENGARUH INOVASI TERHADAP KEBERHASILAN RUMAH MAKAN PANIKI - Gian, Erick Ivan; Novrina, Putri Dwi; Parapaga, Florentina Blandina; Kertayoga, I Putu Ajie Windu; Rizkiyah, Tiara Fitri; Pratama, Angga (Lembaga Kajian Ilmu Sosial dan Politik (LKISPOL), 2023)
This research aims to test the influence of (1) innovation on success. The research design used in thisstudy is quantitative causal research. In this study, the subject of the research was a customer at PanikiDepot, and the object of the study was innovation and success. The sample taken in this study was 79people. Data is collected with interviews, document recordings, and questionnaire methods, as well asanalysed with simple regression analysis. Research results show that: (1) innovation has a significantinfluence on success